Application of Data Envelopment Analysis Technique in Iranian hospitals (A Systematic Review) - Abbas Jahangiri (Tehran University of Medical Sciences, 2016)
Background: Data Envelopment Analysis (DEA) is a mathematical model that evaluates the relative efficiency of Decision Making Units (DMUs) with multiple input and output. The purpose of this paper was systematic study of applying this technique in Iranian hospitals. Materials and Methods: In this systematic review which was conducted in September 2015 and February2016, attempted to search the research which conducted in Iranian hospitals regardless of the time of publication using searching keywords in six scientific databases and with the help of Google search engine. A total of 6,613 researches found. Then, 6,566 researches removed from the study because of the irrelevant, repetitive and Inaccessibility to the full text. Then,  attempted to statistical analysis of 47 remaining researches via Excel 2010 software. Results: 93.6 percent of the researches were published in 2009 onwards. The most research and least research have been conducted in three and eleven provinces respectively. The diversity of output indexes have been more than diversity of input indexes. In 81 percent of researches; input oriented model was used and in 74.5 percent of researches variable returns to scale is assumed. In most studies, referred to Iranchr('39')s inefficient hospitals because of existence of excess resources. Conclusions: In last seven years, the interest of Iranian researchers has increased about DEA application in hospitals especially in Tehran, Yazd and Khoozestan provinces. Scientific and rational use of resources is a proposal to the relevant authorities.